The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s43055-019-0090-z
|View full text |Cite
|
Sign up to set email alerts
|

Value of contrast-enhanced multidetector computed tomography in imaging of symptomatic patients after laparoscopic Roux-en-Y gastric bypass and laparoscopic sleeve gastrectomy

Abstract: Background: To assess the role of contrast-enhanced multidetector computed tomography (MDCT) in the assessment of symptomatic patients following laparoscopic Roux-en-Y gastric bypass and laparoscopic sleeve gastrectomy. Results: We reviewed the studies of 129 cases and found complications in 113 patients: 55 early complications and 48 late complications. All of these complications were diagnosed with intravenous contrast-enhanced MDCT. Statistically significant difference was found between UGIS and MDCT in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Lastly, we found that upper GI series has no role in diagnosing complications such as abscess, internal hernia, port site hernia and intussusception or revealing the cause of intestinal obstruction, where CT scan was able to diagnose. Thus, as compared to UGI series, CT showed superior role in post RYGB complication detection, which is consistent with Bassiouny and Chalabi (28) result who reported higher CT sensitivity series in in the detection of all post RYGB complications.…”
Section: Roux-en-y Gastric Bypass (Rygb) Complicationssupporting
confidence: 87%
“…Lastly, we found that upper GI series has no role in diagnosing complications such as abscess, internal hernia, port site hernia and intussusception or revealing the cause of intestinal obstruction, where CT scan was able to diagnose. Thus, as compared to UGI series, CT showed superior role in post RYGB complication detection, which is consistent with Bassiouny and Chalabi (28) result who reported higher CT sensitivity series in in the detection of all post RYGB complications.…”
Section: Roux-en-y Gastric Bypass (Rygb) Complicationssupporting
confidence: 87%